EXAMINING RICE YIELD IN CHIANG MAI, THAILAND WITH CUSUM CHART - Saithanu, Kidakan; Mekparyup, Jatupat (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The change production of rice in Chiang Mai was examined with the excellent CUSUM chart. The study result capably illustrated         a significant signal since 2010 to 2013. That meant, there was an apparently increase of rice yield in Chiang Mai particularly during 2011-2013.